Religious Extremism and Community Resilience: Case Study of Pakistan (Journal of Politics and International Studies, 2023)
Pakistan is facing, since its inception, extremism in one or the other form. Religious extremism is posing serious existential threat to Pakistan. This paper explains the different factors that contribute in religious extremism in Pakistan. The transformation of a peaceful Sindh province into an extremist region is also elucidated in this research. Multiple Counter Extremism techniques are discussed in this paper. The paper illuminates that how Fatwa can play and important role in countering violent extremism (CVE) in the society. This paper also elaborates the role of imam and mosques in creating community resilience against violence and extremism that is spreading in the society very steadily. The role of religious scholars cannot be ignored in building community resilience among population. The paper illuminates that why these important factors have been failed to create community resilience to counter the prevailing environment of extremism and violence with special reference to Pakistani society. The paper concludes that multiple solutions and steps can maintain community resilience in the society. Revival of teaching of Sufi saints, revision of curriculum, teaching of peace and tolerance, and economic and political inclusion are some of these steps.